Essentials of Pulmonary Lobectomy - Batıhan, Güntuğ (IntechOpen, 2023)
Pulmonary lobectomy is one of the most performed thoracic surgery procedures worldwide. These special operations, which have a higher risk of mortality and morbidity compared to many surgical interventions, are only possible with sufficient theoretical knowledge and experience. Anatomical lung resections, which started with mass ligation of the pulmonary hilum in the 1800s, have become specialized operations that mostly use minimally invasive methods and require individual dissection of hilar structures. However, to date, there has only been a limited number of textbooks on these complex procedures. This book, which discusses the principles of pulmonary lobectomy, was written by experts in the field of thoracic surgery and other subspecialties. Surgical anatomy, VATS lobectomy, RATS lobectomy and intensive care follow-up are discussed in detail. The textbook should be useful for surgery residents and thoracic surgeons seeking to improve their understanding and skills in pulmonary lobectomy.